2018
DOI: 10.3892/etm.2018.6700
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‑574‑3p suppresses proliferation and induces apoptosis of chronic myeloid leukemia cells via targeting IL6/JAK/STAT3 pathway

Abstract: The present study aimed to elucidate the potential roles and regulatory mechanism of microRNA (miR)-574-3p in the development of chronic myeloid leukemia (CML). The expression of miR-574-3p in peripheral blood obtained from patients with CML was examined. Subsequently, miR-574-3p was overexpressed and suppressed in CML K562 cells to further investigate the effects of miR-574-3p on cell proliferation, and apoptosis. Furthermore, a luciferase reporter assay was performed to investigate whether interleukin-6 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Abnormal expression of miRNA has been found in various human cancer types. The genes encoding miR-574-3p are located on chromosomes 4P (4p14 and 4p15) with a tumor inhibitory miRNA function [13]. MiR-574-3p expression levels were decreased in spinal chordoma patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of miRNA has been found in various human cancer types. The genes encoding miR-574-3p are located on chromosomes 4P (4p14 and 4p15) with a tumor inhibitory miRNA function [13]. MiR-574-3p expression levels were decreased in spinal chordoma patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, miR-574 was decreased in liver recipients suffering AR, although these differences were not observed compared with biopsies with AMR [47]. Yang et al [54] showed that miR-574-3p negatively modulates the IL-6/STAT3 pathway. Thus, the decrease in miR-574-3p expression in samples with T cell-mediated rejection [47] could increase pro-inflammatory pathways derived from STAT3 activation [54].…”
Section: Discussionmentioning
confidence: 88%
“…Yang et al [54] showed that miR-574-3p negatively modulates the IL-6/STAT3 pathway. Thus, the decrease in miR-574-3p expression in samples with T cell-mediated rejection [47] could increase pro-inflammatory pathways derived from STAT3 activation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Further, miR-125a promotes the fundamental shift from inflammation to immune suppression by controlling regulatory T cells homeostasis (43). Some evidence suggests that miR-574-3p may also have antiinflammatory function (24). Overall, the presence of several target genes implicated in the regulation of the inflammatory response suggested that the highly expressed miR-125a-5p, miR-574-3p, and let-7-5p subset may play a role in dampening the pro-inflammatory activity of dILC3.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-574-3p has been reported as an oncosuppressor miRNA in different neoplasms, inhibiting cell proliferation, migration and/or metastasis (23)(24)(25). Interestingly, miR-574-3p targets IL6/JAK/STAT3 pathway in hematopoietic cells (24) and TGF-β1 can up-regulate its expression (26). The miRNAs let-7e-5p and miR-125a-5p belong to the miRNA cluster miR-99b/let-7e/miR-125a, a genomic region embedded in the protein coding gene SPACA6 and localized in the q13.41 on chromosome 19.…”
Section: A Restricted Subset Of Mirnas Is Highly Expressed In Dilc3mentioning
confidence: 99%